Energy-efficient algorithm of base station based on dynamic resource grid shut in heterogeneous wireless networks - Wen-xiao SHI; Ji-hong WANG; Ying ZHAO; Ge ZHANG (Tongxin xuebao)
Aiming at solving the problem that the energy efficient effect of current energy saving algorithms of base station based on shutting down carriers/time slots was not ideal,a novel energy saving algorithm of base station based on shutting down RG in heterogeneous networks dynamically was proposed,which called DRGSM algorithm.According to the instantaneous load of the networks,when there were new services to be served,the system would open new resource grids to satisfy their requests for QoS;when the resource grids were free,it shut them down in order to achieve the goal of energy saving.Simulation results show that the proposed algorithm has a better performance in energy deduction and energy saving percentage than current energy saving algorithms of the base station based on shutting down carriers/time slots.